Macroparasites of angelfish Brama brama (Bonnaterre, 1788) in the southern Benguela Current ecosystem. Issue 3 (3rd July 2018) - Mackintosh, AL; Reed, CC; Nunkoo, MAI; King, PH; van der Lingen, CD
Abstract : The angelfish Brama brama is a mesopelagic species distributed circumglobally in temperate to warm-temperate waters, including continental-shelf-edge and upper-slope waters of the Benguela Current ecosystem. Little is known about the parasite assemblage of Benguela B. brama, with only three parasite taxa having previously been documented from this species in the southern Benguela. This study describes the macroparasites recorded from 35 B. brama collected during research surveys off the west coast of South Africa in 2015 and 2016. A total of six macroparasite taxa were documented, including the nematode Anisakis pegreffii, the copepod Hatschekia conifera, the cestode Hepatoxylon trichiuri, an acanthocephalan from the genus Rhadinorhynchus, a monogenean from the family Diclidophoridae, and an unidentified species. Three of these ( He. trichiuri, Rhadinorhynchus sp. and the unidentified species) had not previously been found to infect B. brama . The most prevalent macroparasite taxa were A. pegreffii (94%), the unidentified species (71%) and Ha. conifera (60%). Two of the parasites, Ha. conifera and He. trichiuri, showed seasonal variation in infection, and infection with the latter was positively correlated with host length. These findings increase our knowledge of B. brama biology and contribute to our understanding of the biodiversity of the southern Benguela ecosystem.